Pulse transit time changes in subjects exhibiting sleep disordered breathing. (January 2017) - Chakrabarti, Biswajit; Emegbo, Stephen; Craig, Sonya; Duffy, Nick; O'Reilly, John
Abstract: Introduction: Pulse Transit Time (PTT) represents a non-invasive marker of sleep fragmentation in OSAS. Little is known regarding PTT in sleepy subjects exhibiting nocturnal Inspiratory Flow Limitation (IFL) in the absence of apneas or desaturation. Materials and methods: The IFL cohort was gender and age matched to subjects with OSAS and a cohort where Sleep Disordered Breathing (SBD)/IFL was absent ("Non Flow Limited" or NFL cohort); PTT Arousal index (PTT Ar) defined by number of PTT arousals per hour. Results: 20 subjects meeting criteria for the IFL cohort were aged and gender matched with OSAS and "NFL" subjects. Females comprised 65% of the IFL cohort; the mean BMI of the IFL cohort was significantly higher than the NFL cohort (34.25 v 28.90; p = 0.016) but not when compared to the OSAS cohort (34.25 v 36.31; p = 0.30). The PTT Ar in the IFL cohort (33.67 h) was significantly higher than the NFL cohort (23.89 h) but significantly lower than the OSAS cohort (55.21 h; F = 8.76; p < 0.001). PTT Ar was found to positively correlate with AHI (CC = 0.46; p < 0.001), ODI (CC = 0.47; p < 0.001) and RDI (CC = 0.49; p < 0.001). Within the IFL cohort, PTT Ar positively correlated with age (CC = 0.501; p = 0.024) but not gender and BMI. Conclusion: The PTT Arousal Index increased proportionately with severity of SDB with significantly higher markers of arousal in sleepy subjects exhibiting nocturnal IFL when compared to controls. Subjects exhibiting IFL were predominantly female with an elevated BMI. IFL may thus represent a significant pathogenic entity in the development of daytime sleepiness. Highlights: Pulse Transit Time Arousal Index is high in sleepy snorers exhibiting noctural Inspiratory Flow Limitation. Nocturnal Inspiratory Flow Limitation may be a contributor to daytime sleepiness. Sleepy snorers exhibiting Nocturnal Inspiratory Flow Limitation showed a female predominance and elevated Body Mass Index.